Reading Habits and Attitudes Among University Students: A Review - Alsaeedi, Zubaidah Sadeq Ali; Md. Ngadiran, Nurizah; Abdul Kadir, Zulida; Altowayti , Wahid Ali Hamood; Al-Rahmi, Waleed Mugahed (Journal of Techno-Social, 2021)
Reading is the core element in the learning process. Reading habits and attitudes towards reading is one of the primary concerns in the field of education. A pattern of low reading habits and attitudes among university students is reported by researchers. This paper aims to review the latest literature on reading habits and attitudes among university students. The scope of this literature review was extracted from journal articles and electronic media on the subject of reading habits and attitudes